2019
DOI: 10.21276/ijcmsr.2019.4.2.34
|View full text |Cite
|
Sign up to set email alerts
|

Gynaecological Pelvic Masses: A Clinical Challenge – Radiological Evaluation using Ultrasound and CT with Pathological Correlation

Abstract: Introduction:The evaluation of the female pelvis is a radiological challenge due to the large consortium of differential diagnosis in terms of the origin of masses it houses. In the general population, the prevalence of adnexal lesions is 0.17%-5.9% in asymptomatic women and 7.1%-12% in symptomatic women. The radiological modalities used in evaluation are Ultrasonography,Computed Tomography and MRI. This study strives to demonstrate the role of USG and CT together in detecting the gynecological pelvic lesions,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…Majority of gynecological masses in the current study were ovarian (66.7%), while uterine masses were 33.3% of cases that is consistent with Sharma et al [19] who reported that ovarian masses represented 66% of the diagnosed gynecolical masses. Cass and Newton [22] also This is probable because the majority of uterine lumps are leiomyomas, which are asymptomatic and do not prompt patients to seek medical attention.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Majority of gynecological masses in the current study were ovarian (66.7%), while uterine masses were 33.3% of cases that is consistent with Sharma et al [19] who reported that ovarian masses represented 66% of the diagnosed gynecolical masses. Cass and Newton [22] also This is probable because the majority of uterine lumps are leiomyomas, which are asymptomatic and do not prompt patients to seek medical attention.…”
Section: Discussionsupporting
confidence: 91%
“…Other lesions were endometrial polyp (6.1%), endometrial hyperplasia (3%), and adenomyosis (3%). Similarly, Abd-Elmageed et al [20] and Sharma et al [19] found that the most prevalent benign tumors were leiomyomas. This is also consistent with the well documented data that uterine leiomyomas are the most prevalent benign pelvic tumor in women.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation